Pengaruh Personality dan Gender terhadap Wawasan Lingkungan Siswa (Students Ecological Word View) - Asrar Habibie (IJEEM - Indonesian Journal of Environmental Education and Management, 2017)
The purpose of this research is to know students perspective to the environmental insights related to personality and gender, on the subjects of biology. This research use method ex post facto research with ANAVA 2x2 models. The instrument used in this study is a test. A view of students to the environment that are constructed in the human mind then reflected became the basis for interacting with the environment and action to the environment. Personality is the human nature that dynamic to respond and react and interact relatively stable with other people or the environment in accordance with the underlying dimensions of personality that is conscientiousness, agreeableness, neuroticism, openness, extraversion in order to achieve personal goals. Gender is equity in the opportunity to actively participate in social programs based on gender differences factor. This means that the gender variable divide students according to gender. Male and female student have diversity of looking at the surrounding environment so that environmental insight of students who have a high personality better than the environment insight students have low personality. Environmental insight into the male student better than woman student.